Crotalaria spectabilis as a source of pyrrolizidine alkaloids and phenolic compounds: HPLC-MS/MS dereplication and monocrotaline quantification of seed and leaf extracts - Scupinari, Tamires; Mannochio Russo, Helena; Sabino Ferrari, Anna Beatriz; da Silva Bolzani, Vanderlan [UNESP]; Dias, Waldir Pereira; de Oliveira Nunes, Estela; Hoffmann-Campo, Clara Beatriz; Zeraik, Maria Luiza (Wiley, 2020)
Introduction: Crotalaria spectabilis is an important species used as a pre-plant cover for soybean crops to control the proliferation of endoparasitic nematodes. Species from the Crotalaria genus are known for presenting pyrrolizidine alkaloids (PAs) in their composition, however, C. spectabilis is still considered chemically under-explored. Objective: The goal of this manuscript is the development and validation of a method for PAs and flavonoids identification and quantification of C. spectabilis seeds and leaves, a toxic plant used for nematode proliferation control in soil, especially in soybean crops. Materials and methods: Seeds and leaves extracts were analysed by high-performance liquid chromatography coupled to tandem mass spectrometry (HPLC-MS/MS) for the identification of the compounds. Results: PAs and phenolic compounds could be identified in both samples based on the MS/MS fragmentation pattern. Molecular formulas of the annotated compounds were confirmed by ultra-high-performace liquid chromatography-quadrupole time-of-flight (UHPLC-QToF), and monocrotaline could also be confirmed by standard comparison. The quantification of monocrotaline was performed by HPLC-MS/MS, resulting in 123 times higher monocrotaline content in seeds than in the leaves, which could explain its efficiency in combating nematode proliferation in soil. Conclusion: This was the first report of phenolic compounds in C. spectabilis. The current study highlights the importance of C. spectabilis for nematode control due to the presence of toxic PAs, and the employment of analytical techniques for identification and quantification of compounds present in the extracts.
Keywords: Crotalaria spectabilis; nematode control; pyrrolizidine alkaloids; toxic plant